Inclusive Green Growth in Latin America and the Caribbean - World Bank (Washington, DC, 2014)
Argentina has expanded the use of its portion of the Parana-Paraguay waterways system for the transportation of soy and other bulk commodities through an innovative tolling system that self-finances the dredging and maintenance of the rivers. Brazil, in turn, is pursuing a 'green trucking' strategy to improve efficiency of its cargo haulage industry, reduce petroleum usage, and curb pollution from trucking. For the entire hemisphere, the expansion of the Panama Canal will bring post-Panama vessels and introduce greater scale economies in shipping. The following sections of this paper provide a more detailed review of the sectoral objectives, challenges, and way forward in making Latin America and Caribbean (LAC) growth greener and more inclusive. It looks back over the achievements of the demand sectors of urban development and infrastructure services, energy, urban transport, and water and sanitation, as well as natural resources and rural development since Rio 1992. It highlights the achievements in those areas, and the ability of those accomplishments to establish a robust path for the region to inclusive green growth.